Host‐Guest Chemistry of Linked β‐ and γ‐Cyclodextrin Dimers and 1‐ and 2‐Naphthyl‐Sulfonamide Substituted Poly(acrylate)s in Aqueous Solution. Issue 4 (3rd February 2017) - McTernan, Hamish L.; Ngo, Huy T.; Pham, Duc‐Truc; Clements, Philip; Lincoln, Stephen F.; Wang, Jie; Guo, Xuhong; Easton, Christopher J.
Abstract: Host‐guest complexation by β‐ and γ‐cyclodextrin and their four succinamide‐linked dimers of the naphthyl substituents of four randomly substituted poly(acrylate)s in twenty‐four aqueous systems has been characterised. Complexation occurs through entry of the naphthyl substituents into the cyclodextrin annuli. The naphthyl substitution position, the length of the tether attaching the naphthyl substituent to the poly(acrylate) backbone and the size and stereochemistry of the cyclodextrin hosts determine the relative stabilities of poly(acrylate) intra‐strand complexes in dilute solution and the formation of inter‐strand cross‐links in more concentrated solution. Abstract : Intra‐ and inter‐strand ditopic complexation of the N ‐(6‐aminohexyl)‐2‐naphthyl‐sulphonamide substituents of a substituted poly(acrylate) by a succinamide linked β‐cyclodextrin dimer, and variations of this occur in related systems in aqueous solution.